Majd al-Din al-Firuzabadi (1329-1415) : a polymath on the eve of the early modern period - Strotmann, Vivian. (Islamic History and Civilization, 2016)
In Majd al-Dīn al-Fīrūzābādī (1329-1415): A Polymath on the Eve of the Early Modern Period , Vivian Strotmann provides a detailed reconstruction of the famous lexicographer's and travelling scholar's life and works. The 'author of the Qāmūs al-muḥīṭ ' is widely known for his Arabic lexicon, which overshadows the astounding breadth of his writing. This polymathic aspect is elucidated through detailed reconstruction of al-Fīrūzābādī's corpus, including examination of works that were considered lost and misapprehensions concerning ascriptions of authorship. Through minute analysis of biographical sources, the book shows al-Fīrūzābādī's development as a scholar, his central role in the defence of Ibn al-ʿArabī's teachings and thereby his importance as a powerful intellectual in Timurid times and for developments during the Early Modern Period.